Analisis Jenis Kalimat Berdasarkan Jumlah Klausanya pada Cerpen dalam Buku Bahasa Indonesia SMP - Adam, Marsadi; Afrizal, Daviq (Program Studi Pendidikan Bahasa dan Sastra Indonesia FKIP Universitas Islam Riau, 2024)
The existence of short stories is very useful, one of which is as a means of conveying messages. Therefore, the message to be conveyed through short stories must be clear and unambiguous so that readers can understand the plot or message in the short story. This research is important to do because it is to find out the ambiguity or clarity of meaning and the accuracy of writing sentences in short stories in the Indonesian Language Student book for Junior High School/MTs Class 9. This research method is descriptive qualitative. This study aims to find out how many types of sentences are based on the number of clauses in short stories in the Indonesian Language Student book for Junior High School/MTs Class 9 and to find out the clarity of the meaning of sentences, the accuracy of writing sentences and the function of sentences in short stories. The results of this study are the discovery of the use of types of sentences based on the number of clauses and seen from their ambiguity, namely unambiguous simplex sentences totaling 109 sentences; ambiguous simplex sentences totaling 1 sentence; unambiguous compound sentences totaling 19 sentences; ambiguous compound sentences totaling 1 sentence; unambiguous complex sentences totaling 58 sentences; complex compound sentences totaling 7 sentences.